Pengaruh Perdagangan Internasional Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2010-2018: Effect Of International Trade On Indonesia's Economic Growth In 2010-2018 - Aprianto Ladolo; Sri Rahayu Husen; Suwardi Zakaria (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2022)
This study aims to determine the relationship of international trade to economic growth in Indonesia in 2010-2018, using quantitative multiple friction analysis using secondary data in the form of export, import, and Gross Domestic Product data of Indonesia. The analysis results showed that the export variable t-test on Indonesia's economic growth had a negative effect and import variables on economic growth. For the F test that export and import variables negatively affect economic growth.